Predicting the potential distribution of stingless bee, Tetragonula iridipennis in India using MaxEnt and CMIP6 climate projections - V. Karuppaiah; R. Maruthadurai; Bappa Das; P. S. Soumia; Ankush Gadge; Chandrashekhar Pote; Dhananjay Shirsat; Trupti Pandit; Sanket Sawant; S. V. Ramesh; Vijay Mahajan (Scientific Reports, 2024)
Abstract Tetragonula iridipennis Smith, commonly known as the stingless bee or ‘dammer bee’, is a key native species that pollinates a wide variety of horticultural crops, including onions, in India. Climate change significantly affects species distribution and habitat suitability. This study utilized Maximum Entropy Modeling (MaxEnt) to predict the current and future distribution of T. iridipennis in India. By modeling the species’ potential distribution using both historical climate data (1970–2000) and future projections for 2050 and 2070 under two socio-economic scenarios, SSP126 (low-emission) and SSP585 (high-emission), the study provided accurate predictions. The area under the receiver operating characteristic curve (AUC) for model training and testing was 0.848 and 0.830, respectively, indicating strong model accuracy. Additionally, the Continuous Boyce Index (CBI) values for training and testing were 0.966 and 0.907, while the True Skill Statistic (TSS) values were 0.510 and 0.484. These metrics confirm that the model effectively distinguishes between suitable and unsuitable habitats for the species. The two most influential variables determining 84.9% of T. iridipennis’s potential distribution were temperature seasonality (bio4; 66.2%) and mean temperature of the coldest quarter (bio11; 18.7%). The ideal zone for these variables were 155–170 and 13–28, respectively. The model indicated that the potential distribution of T. iridipennis is concentrated primarily in central and southern peninsular India, with the species’ habitat predicted to expand under both SSP126 and SSP585 scenarios. This study provides a detailed overview of the current and potential future habitable areas for T. iridipennis in India, offering insights that could help guide conservation efforts for this important native pollinator.